Developing students’ social and communication skills through gaming sports - Antipov, A.V.; Shustova, E.V.; Nikolaev, P.P.; Vaseltsova, I.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the educational potential of team sports in developing the social and communication skills of university students and to experimentally demonstrate the effectiveness of their use in the university educational process. Methods and structure of the study. The study was conducted over two semesters at the university’s sports facilities and involved 68 first-, second- and third-year students. The students were divided into an experimental and a control group of 34 students each, who were identical in terms of physical fitness and lack of regular experience in team sports, ensuring their initial homogeneity. The experimental group followed a specially designed programme based on the systematic use of five-a-side football, volleyball and basketball, with the structure of the sessions aimed at developing skills in teamwork, rapid information exchange and coordination of actions in dynamic game situations. Sessions took place twice a week and combined training and game-based activities. Results and conclusions. Analysis of the data revealed the dynamics of the development of students’ social and communication skills under the influence of systematic participation in team sports. The results of the study showed that the systematic use of five-a-side football, volleyball and basketball has a marked positive effect on the development of students’ social and communication skills. During the experiment, participants in the experimental group demonstrated significant improvements across all key indicators, including communicative tolerance, the level of group inclusion and the effectiveness of team interaction.